Removal of Heavy Metal Ions by Activated Carbon Modified by Calcium - Leese, Emily; Genesan, Christopher; Singhal, Fatma; Azadi, Peer (Journal of Green Energy and Environmental Engineering, 2024)
The migration and transformation of heavy metal ions in environment, especially water bodies, have been a focal research topic in environmental science. Particularly in alkaline environments, the mobility and bioavailability of Arsenic (As) are relatively high, increasing the complexity of remediation. Activated carbon, owing to its rich pore structure and good stability, is widely used in the remediation of heavy metal-contaminated water bodies. However, its ability to immobilize As is limited by electrostatic repulsion caused by its surface negative charge. Studies have shown that introducing cations can effectively enhance the immobilization capacity of activated carbon for As. Calcium (Ca) has become a key research focus due to its high affinity for As. Nevertheless, the interaction mechanisms between different components of activated carbon and As in the presence of calcium under alkaline conditions remain unclear, and the immobilization effects of activated carbon loaded with different forms of calcium-based materials require further investigation. The main experimental results showed that activated carbons, labeled BC and CBC, were prepared by pyrolysis of wheat straw without and with calcium carbonate addition, respectively, at 850°C. Adsorption results indicated that the adsorption of As(V) by both BC and CBC conformed to the Langmuir isotherm model, characteristic of monolayer adsorption, with theoretical maximum adsorption capacities of 536.3 mg·g⁻¹ and 610.0 mg·g⁻¹, respectively. The adsorption kinetics for both followed the pseudo-second-order model and were controlled by intraparticle diffusion. Thermodynamic analysis revealed that the adsorption processes of As(V) onto BC and CBC were spontaneous, endothermic, and accompanied by an increase in entropy. Mechanistic studies indicated that the removal of As(V) by BC and CBC primarily relied on co-precipitation.